Framing Pemberitaan Media Online mengenai Bentrokan antara Anggota Front Pembela Islam (FPI) dan Anggota Kepolisian - Said Romadlan; Dini Wahdiyati (UMSU, 2022)
Basically a news story must be objective, balanced, and unbiased. But in practice there is often a news story that is not objective, unbalanced, and biased. This is because there are interests that influence the pattern of media content so that the news tends to be biased. One form of media bias is framing, which is selecting certain issues and removing other issues, and highlighting certain facts and covering up other facts. With regard to framing practices, this article focuses on two issues, firstly, how to frame the news of clashes between members of the Islamic Defenders Front (FPI) and police members in the online media Kompas.com and Tirto.id? Second, what are the factors that influence the framing of the news of clashes between members of the Islamic Defenders Front (FPI) and members of the police in the online media Kompas.com and Tirto.id? To understand the framing of the two online media, used framing analysis model Robert Entman as research method. Data collection uses documentation in the form of news of clashes between FPI members and police in Kompas.com and Tirto.id. While the data analysis is text analysis and context analysis. The results of the study showed first, framing Kompas.com further highlight the fact of the attacks carried out by FPI members against members of the Police that resulted in 6 FPI members being shot dead. While framing the Tirto.id further highlights the fact of the shootings committed by police members against FPI members that led to the deaths of 6 FPI members. Second, the factor that influences framing is the practice of organizations (media routines) of both online media. Thus, the both of online media in their coverage of clashes between FPI members and police members tend to be biased because it is influenced by their respective of media practices.